Analysis of Resistance Among Teachers and Staff to Working Hours Discipline Policies at Bunga Mawar Private Junior High School in Gunungsitoli City - Bebalazi Lase; Sukaaro Waruwu; Syah Abadi Mendrofa (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to describe the forms of resistance exhibited by teachers and staff toward work hour discipline policies, identify the factors causing such resistance, and describe the school’s efforts to address teachers’ and staff’s resistance to work hour discipline policies at Bunga Mawar Private Junior High School in Gunungsitoli City. This study employs a qualitative approach using a case study design. Data collection techniques included in-depth interviews, non-participant observation, and documentation. Research informants consisted of the principal, teachers, the vice principal, subject teachers, and administrative staff, all selected through purposive sampling. Data analysis was conducted through data reduction, data presentation, and the drawing of conclusions and verification. The results of the study indicate that teachers’ and staff members’ resistance to the work hours policy is mostly passive and indirect. Forms of resistance include arriving late, irregularities in filling out attendance records, the habit of arriving only according to their teaching schedules, leaving during work hours for personal matters without clear notification, and complaints regarding the flexibility of work hours. Factors contributing to this resistance include long-standing work habits, differing interpretations of work hours, distance from home, transportation challenges, family obligations, teaching workload, additional duties, insufficiently detailed policy communication, inconsistent supervision, and perceptions of fairness in the enforcement of rules. The school’s efforts to address this resistance include policy outreach, dialogue, involving teachers and staff in evaluations, individual coaching, rewards, graduated sanctions, and review of attendance records. Overall, work-hour discipline policies can be implemented more effectively if they are applied clearly, fairly, communicatively, participatively, and humanely.